A Neonate with Multiple Causes of Apparent Life-Threatening Event (ALTE): A Case Report - Maliheh Kadivar; Leila Shahbaznejad (Mashhad University of Medical Sciences, 2016)
Apparent life-threatening event (ALTE) is a major cause of neonatal emergency visits. In this paper, we presented the case of a three-day-old neonate with multiple indications of ALTE. The patient was referred to the emergency department due to a cyanotic attack before admission. The neonate woke a few hours after breastfeeding and turned blue while crying, which was resolved spontaneously within a few seconds. During ALTE, moderate hypotonia was observed in the neonate, while the physical examination was not remarkable. Primary sepsis workup and electrolyte measurement were performed, the results of which were mostly within the normal limits, with the exception of low levels of calcium, magnesium, and vitamin D. Moreover, the infant had primary hypothyroidism and received treatment with intravenous antibiotics initially accompanied by magnesium and calcium for a few days. Treatment continued with vitamin D and levothyroxine, and the neonate was discharged from the hospital in good overall condition without further ALTE episodes. All infants must be evaluated in terms of common indications of ALTE, such as electrolyte imbalance. In addition, other probable causes of ALTE should be investigated through obtaining a detailed medical history and proper physical examination. According to the literature, neonates are likely to present with more than one manifestation of ALTE.